Pengaruh Manajemen Laba, Sales Growth, Transfer Pricing, dan Umur Perusahaan terhadap Praktik Penghindaran Pajak - Noviyanti Dewi; Wahyu Nurul Hidayati (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to determine the effect of earnings management, sales growth, transfer pricing, and company age on tax avoidance practices. This type of research is quantitative research. The data used in this study are secondary data. The population in this study are non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2018-2022. The total population in this study were 114 companies. The sampling technique used purposive sampling and obtained 15 companies with a research period of 5 years so that 75 sample data were obtained. The data analysis used in this research is descriptive statistics, panel data regression test, classical assumption test, and hypothesis testing. The results showed that earnings management and transfer pricing had no significant effect on tax avoidance, while sales growth and company age had a significant effect on tax avoidance.